Recent advances of membrane-based hybrid membrane bioreactors for wastewater reclamation - Kim, Jeonghwan; Wu, Bing; Jeong, Sanghyun; Jeong, Seongpil; Kim, Minseok (Frontiers in Membrane Science and Technology, 2024)
Membrane bioreactor (MBR) is an advanced wastewater treatment technology, which has been established for more than three decades. In MBRs, membrane separation allows not only rejecting microorganisms/greater-sized molecules but decoupling hydraulic retention time (HRT) and solid retention time (SRT). Low-pressure driven, porous membranes have been widely used in MBRs, but their performances are mainly limited for wastewater reuse applications. Recently, many attempts have been made to combine desalination technologies to advance hybrid MBR processes for wastewater reclamation. Nanofiltration (NF) and reverse osmosis (RO) have been applied with the MBRs to improve effluent quality, and their advantages and challenges have been well reported in terms of rejection efficiency, operational energy, fouling control and recovery of retentate stream. Alternatively, the direct introduction of non-pressurized desalination technologies such as forward osmosis (FO) and membrane distillation (MD) into MBR processes for wastewater reclamation or probably for microbial activity have been considered substantially due to their low energy consumption and excellent rejection efficiency of solid materials. However, several technical limitations still need to be resolved to commercialize hybrid FO-or MD-MBR processes. This paper reviews recent advances of MBR technology integrated with desalination technologies for wastewater reclamation and suggests perspectives to optimize membrane-based hybrid MBR process.